Hiperrealitas dalam Permainan Video Daring: Simulasi, Simulakra, dan Hiperrealitas Garena Free Fire - Anak Agung Ngurah Agung Suryadipta Wardhana (PERSPEKTIF, 2022)
The aim of this article is to dissect the hyperreality side of the online video game Free Fire. Hyperreality can be seen from the war simulations contained in the course of the game, the weapons used, the selected characters that players can use, to the virtual world that becomes the battle arena. This article uses Jean Baudrillard's hyperreality concept which can show the sides of the game that make up the hyperreality conditions of the players, so that players can no longer distinguish between reality and the artificial. With a qualitative approach, this article explores and understands the meaning in the game by interpreting a collection of texts and then analyzing it by prioritizing the human side. The conclusion of this study shows that players are trapped in a world that no longer refers to a real prototype as usual simulations do. The simulacra contained in the game is in the form of a gameplay that does not refer to real warfare, character and weapon selection, team strategy as a productive form of simulacra, and the battle arena as a natural form of simulacra. The hyperreality in the form of war simulacra and scenes of violence is getting stronger with the interaction feature between players and the proliferation of e-sports competition ecosystems in Indonesia that offer big prizes.